2022
DOI: 10.32670/fairvalue.v5i1.2224
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh current ratio, debt to equity, debt to asset, return on asset, return on equity, net profit margin dan price earning ratio terhadap harga saham

Abstract: The study aims to determine and analyze the effect of the variable current ratio, debt to equity, debt to assets, return on assets, return on equity, net profit margin, and price earning ratio on stock prices in the infrastructure company PT BEI. This type of research is a quantitative research using secondary data. The sample used in this study were 38 infrastructure companies on the Indonesia Stock Exchange during the 2018-2021 period that met the criteria in this study. Sampling in this study using purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 4 publications
2
8
2
5
Order By: Relevance
“…On the other hand, if the value of the Debt to Equity Ratio of a telecommunications company decreases, the value of the company's share price will also decrease. On the contrary, the findings are not in line with previous discovery who found evidence that the Debt to Equity Ratio had no effect on stock prices (Nurdin, 2015;Octavianty & Aprilia, 2014;Priliyastuti & Stella, 2017). 3) ROA have t-statistic value of -5.054425, and the probability value is 0.0000.…”
Section: Effect Of Current Ratio (Cr) Return On Asset (Roa) Debt To E...contrasting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, if the value of the Debt to Equity Ratio of a telecommunications company decreases, the value of the company's share price will also decrease. On the contrary, the findings are not in line with previous discovery who found evidence that the Debt to Equity Ratio had no effect on stock prices (Nurdin, 2015;Octavianty & Aprilia, 2014;Priliyastuti & Stella, 2017). 3) ROA have t-statistic value of -5.054425, and the probability value is 0.0000.…”
Section: Effect Of Current Ratio (Cr) Return On Asset (Roa) Debt To E...contrasting
confidence: 93%
“…Then it can be seen that the value ofprobability is less than 0.05 (0.0165<0.05) so it can be concluded that the current ratio variable has a significant effect on stock prices and it means that the H1 hypothesis is accepted. This finding is in line with previous research who found evidence that the Current Ratio had a significant effect on stock prices (Nurdin, 2015;Octavianty & Aprilia, 2014;Priliyastuti & Stella, 2017). These findings show that if the current ratio value of a telecommunications company increases or decreases, it will not significantly affect the high or low value of stock prices.…”
Section: Effect Of Current Ratio (Cr) Return On Asset (Roa) Debt To E...supporting
confidence: 92%
“…ROA ialah perbandingan yang menunjukkan kinerja emiten dalam menciptakan profit yang memanfaatkan seluruh asetnya. (Priliyastuti & Stella, 2017). Menurut Sartono (2018) Rasio yang disebut ROA menunjukan seberapa menguntungkan suatu perusahaan dalam menggunakan asetnya.…”
Section: Return On Assetsunclassified
“…Penjelasan diatas di dukung oleh penelitian terdahulu yang dilakukan oleh Meilani et al (2023) dalam penelitiannya mengatakan bahwa EPS tidak memiliki pengaruh positif dan signifikan terhadap Harga Saham.…”
Section: Uji Hipotesis Secara Simultan (Uji F)unclassified